2014
DOI: 10.1159/000358300
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Megacystis: Experience of a Single Tertiary Center in Switzerland over 20 Years

Abstract: Objectives: Megacystis (MC) is rare and often associated with other structural and chromosomal anomalies. In euploid cases with early oligohydramnios, prognosis is poor mainly due to pulmonary hypoplasia and renal damage. We report our experience of the past 20 years. Methods: A retrospective review of cases with prenatally diagnosed MC was performed. Complete prenatal as well as postnatal medical records from 1989 to 2009 were reviewed focusing on diagnostic precision, fetal interventions [vesicocentesis (VC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Previous studies have investigated fetal urine production according to gestational age in healthy fetuses without reporting fetal bladder dimensions. Miscellaneous criteria have been used in the literature for defining megacystis in the second and third trimesters, ranging from bladder length > 99 th percentile for gestational age in the absence of a nomogram, to the most commonly used definition of fetal bladder failing to empty during a period of 45 min. There has not yet been a prospective study published that has elucidated normal bladder dimensions during the second and third trimesters of pregnancy and defined a threshold for pathological enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated fetal urine production according to gestational age in healthy fetuses without reporting fetal bladder dimensions. Miscellaneous criteria have been used in the literature for defining megacystis in the second and third trimesters, ranging from bladder length > 99 th percentile for gestational age in the absence of a nomogram, to the most commonly used definition of fetal bladder failing to empty during a period of 45 min. There has not yet been a prospective study published that has elucidated normal bladder dimensions during the second and third trimesters of pregnancy and defined a threshold for pathological enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal diagnosis of fetal megacystis represents a diagnostic challenge [30,31]. In the first trimester, the longitudinal bladder diameter (>7 mm) appears to be a useful sonographic marker for fetal aneuploidy [32].…”
Section: Discussionmentioning
confidence: 99%
“…The fetal bladder can easily be visualized as a round or oval structure without echogenicity between two umbilical arteries in the pelvis by routine ultrasonography (1). Although urogenital anomalies are common, megacystis (MC) is very rare and its incidence is reported to be 0.06% (2,3). It has been reported that several genetic, environmental and teratogens may be responsible for urinary tract abnormalities (4).…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal diameter of the normal bladder in the first trimester is usually <6mm (2). The diagnosis of early-onset MC is made when the bladder is detected more than 7mm in the first-trimester ultrasonography.…”
Section: Introductionmentioning
confidence: 99%